Cyber security breaches survey, 2021 (UK Data Service, 2021)
The Cyber Security Breaches Survey, 2021 (CSBS) was run to understand organisations' approaches and attitudes to cyber security, and to understand their experience of cyber security breaches, especially in light of the COVID-19 pandemic. The aim of the survey was to support the Government by providing evidence that can inform policies which help to make Britain a safer place to do business online. Details of changes for the 2021 survey can be found in the Technical Annex documentation.